THE ASSOCIATION BETWEEN VITAMIN D DEFICIENCY AND ATTENTION AND MEMORY IMPAIRMENTS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article systematically reviews the impact of vitamin D deficiency on attention, memory, and related cognitive functions in children. Epidemiological studies, observational data, and interventional trials examining the association between serum 25-hydroxyvitamin D (25(OH)D) levels and attention deficits, memory impairment, and executive functioning in children are analyzed. Key risk factors—age, sex, sunlight exposure, nutritional status—and preventive strategies such as vitamin D supplementation and lifestyle modification are also discussed. The findings highlight the potential importance of adequate vitamin D status in supporting cognitive performance in the pediatric population.